PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING (SFE) TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA - Pancatama, Yogi; Anwar, Syahrul; Zakaria, Muahor (STKIP La Tansa Mashiro, 2023)
The purpose of this research is to find out the influence of the student facilitator and explaining learning model on students’ mathematical reasoning abilities. The research subject were class X students SMK Negeri 1 Cikulur for the 2022/2023 academic year. The method used is quantitative with a Pretest-Posttest Control Group Design. The sampling technique was carried out using random sampling which was chousen randomly. The data collection technique used was a question testin the forem of a description. Data analysis technique contain two types, namely quantitative data consisting of descriptive and inferential statistic. Hypothesis testing was carried out using a paired sample test (t test). The findings show that in the experimental class the avarage pretest value was 30,00 and avarage posttest value was 78,17. In the control class, the avarage pretest value obtained a result of 28,50 and an avarage posttest score of 73,33. It means if a comparison is made between the two samples there is a significanet difference that is value 3,34, where the experimental class is superior by using the model student facilitator and explaining learning compared to the control class using the expository learning model. Based on the results of hypothesis testing, where the sig (2-tailed) value is 0,000 0,05, it can be said that Ho is rejected and Ha is accepted, which meanes there is an influence of the student Learning model facilitator and explaining on the mathematical reasoning ability of the student. Tujuan penelitian ini untuk mengetahui pengaruh dari model pembelajaran student facilitator and explaining terhadap kemampuan penelaran matematis siswa. Subjek dalam penelitian ini adalah siswa kelas X SMK Negeri 1 Cikulur tahun ajaran 2022/2023. Metode yang digunakan adalah kuantitatif dengan desain penelitian Pretest-postest Control Group Design. Teknik pengambilan sampel dilakukan dengan mengunakan Random Sampling yang dipilih secara acak. Teknik pengumpulan data yang digunakan berupa tes soal berbentuk uraian. Teknik analisis data memuat dua jenis yakni data kuantitatif yang terdiri dari statistika deskriptif dan inferensial. Pengujian hipotesis menggunakan Uji paired sampel t test. Hasil temuan menunjukan pada kelas eksperimen rata-rata nilai pretest sebesar 30,00, dan rata-rata nilai posttest sebesar 78,17. Sedangkan kelas kontrol rata-rata nilai pretest memperoleh hasil sebesar 28,50, dan rata-rata nilai posttest sebesar 73,33. Artinya jika dilakukan suatu perbandingan antara dua sampel maka terdapat selisih nilai yang cukup signifikan yaitu sebesar 3,34 dimana kelas eksperimen lebih unggul dengan menggunakan model pembelajaran student facilitator and explaining dibandingkan kelas kontrol yang menggunakan model pembelajaran ekspositori. Berdasarkan hasil uji hipotesis diperoleh nilai sig.(2-tailed) 0,000 < 0,05 maka dapat dikatakan bahwa H0 ditolak dan Ha diterima, yang berarti terdapat pengaruh model pembelajaran student facilitator and explaining terhadap kemampuan penalaran matematis siswa.